A novel screening method for free non-standard amino acids in human plasma samples using AccQ·Tag reagents and LC-MS/MS. Issue 4 (5th January 2023) - Ng, Daniel H. J.; Chan, Li Yan; Fitzner, Laura; Keppler, Julia Katharina; Ismail, Shareef M.; Hird, Simon; Hancock, Peter; Karin, Schwarz; Tobias, Demetrowitsch
Abstract : A novel screening method was developed for free non-standard amino acids in complex biological matrices using an AccQ·Tag™ derivatization kit, which reduces the need for analytical standards during method development. Abstract : There are at least 500 naturally occurring amino acids, of which only 20 standard proteinogenic amino acids are used universally across all organisms in the synthesis of peptides and proteins. Non-standard amino acids can be incorporated into proteins or are intermediates and products of metabolic pathways. While the analysis of standard amino acids is well-defined, the analysis of non-standard amino acids can be challenging due to the wide range of physicochemical properties, and the lack of both reference standards and information in curated databases to aid compound identification. It has been shown that the use of an AccQ·Tag™ derivatization kit along with LC-MS/MS is an attractive option for the analysis of free standard amino acids in complex samples because it is fast, sensitive, reproducible, and selective. It has been demonstrated that the most abundant quantitative transition for MS/MS analysis of 6-aminoquinolyl- N -hydroxysuccinimidyl carbamate (AQC) derivatized amino acids corresponds to the fragmentation of the molecule at the 6-aminoquinoline carbonyl group producing a common m / z 171 fragment ion and occurs at similar mass spectrometry collision energy and cone voltages. In this study, the unique properties of AQC derivatized amino acids producing high intensity common fragment ions, along with chromatographic separation of amino acids under generic chromatography conditions, were used to develop a novel screening method for the detection of trace levels of non-standard amino acids in complex matrices. Structural elucidation was carried out by comparing the MS/MS fragment ion mass spectra generated with in silico predicted fragmentation spectra to enable a putative identification, which was confirmed using an appropriate analytical standard. This workflow was applied to screen human plasma samples for bioactive thiol-group modified cysteine amino acids and S -allylmercaptocysteine (SAMC), S -allylcysteine sulfoxide (SACS or alliin) and S -propenylcysteine (S1PC) are reported for the first time to be present in human plasma samples after the administration of garlic supplements.